2012
DOI: 10.1038/nn.3269
|View full text |Cite
|
Sign up to set email alerts
|

Closed-loop optogenetic control of thalamus as a tool for interrupting seizures after cortical injury

Abstract: Cerebrocortical injuries, such as stroke, are a major source of disability. Maladaptive consequences can result from post-injury local reorganization of cortical circuits. For example, epilepsy is a common sequela of cortical stroke, yet mechanisms responsible for seizures following cortical injuries remain unknown. In addition to local reorganization, long-range, extra-cortical connections might be critical for seizure maintenance. Here we report in rats the first evidence that the thalamus – a structure remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
502
3
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 513 publications
(528 citation statements)
references
References 32 publications
15
502
3
1
Order By: Relevance
“…This cell type specificity allows manipulation of specific circuits and thus more targeted manipulations, which should help pinpoint the circuits and molecular mechanisms that underlie diseases. Optogenetic approaches have been used in rodents to probe neural circuits for several neurological/neurodegenerative diseases, including Parkinson's disease [78,79], epilepsy [80,81], and stroke [26,82]. In the next sections we will first introduce optogenetics and its developments, and then review the current understanding of remapping and recovery after stroke from recent studies using peripheral and optogenetic stimulation, as well as the use of optogenetic stimulation to enhance post-stroke recovery.…”
Section: Current Brain Stimulation Techniques Used To Study Stroke Rementioning
confidence: 99%
“…This cell type specificity allows manipulation of specific circuits and thus more targeted manipulations, which should help pinpoint the circuits and molecular mechanisms that underlie diseases. Optogenetic approaches have been used in rodents to probe neural circuits for several neurological/neurodegenerative diseases, including Parkinson's disease [78,79], epilepsy [80,81], and stroke [26,82]. In the next sections we will first introduce optogenetics and its developments, and then review the current understanding of remapping and recovery after stroke from recent studies using peripheral and optogenetic stimulation, as well as the use of optogenetic stimulation to enhance post-stroke recovery.…”
Section: Current Brain Stimulation Techniques Used To Study Stroke Rementioning
confidence: 99%
“…Several early studies of optogenetics in vitro and in animal models of epilepsy have shown promising results. The earliest application of optogenetics to epilepsy was by Tønnesen et al [33], who demonstrated that halorhodopsin-an inhibitory chloride pump-was capable of suppressing epileptiform activity in hippocampal organotypic slice cultures. More recently, 3 groups have demonstrated that inhibition of particular targets can interrupt seizures in vivo in rat models of epilepsy.…”
Section: Future Directionsmentioning
confidence: 99%
“…Thalamic relays are also thought to mediate the benefits from lesions and electrical stimulation of the cerebellum for epilepsy, but this circuit and its influence is less clearly defined [30][31][32]. More precise work identifying and manipulating neural signaling within the thalamocortical network is currently being performed [33].…”
mentioning
confidence: 99%
“…Une large fraction des neurones thalamocorticaux (excitateurs) interconnectés avec la région corticale lésée étaient ensuite photosensibilisés par expression de la NpHR à l'aide d'un vecteur viral. Le protocole d'illumination de ces neurones en boucle fermée s'est révélé capable de stopper les crises d'épilepsie moins d'une seconde après leur apparition, et ce jusqu'à un an après implantation du système chez les animaux [51]. Dans une deuxième étude, un modèle d'épilepsie du lobe temporal était obtenu chez la souris par lésion pharmacologique focale de l'hippocampe à l'acide kaïnique.…”
Section: Perspectives Thérapeutiques Offertes Par Les Outils Optogénéunclassified